The Bauhaus its impact on the world of design (Northbrook, Ill. Roland Collection, 1976)
Film shows that of all art institutions in the 1920's, the Bauhaus was the most intensive in its approach to the task of aestheticizing the modern technical world. At the same time it indicates the importance of designing in general, for without it, the human need for beauty would remain unsatisfied.
VHS/Beta format.
Director, Detten Schliermarcher ; original music, Hans Posegga.
Keywords: Bauhaus; Art, German; Art, German -- 20th century; Design -- Germany -- History -- 20th century